Perilaku Komunikasi Kyai Dengan Masyarakat Sekitar Pondok Pesantren Nurul Yaqin Ringan-Ringan - Romi Altavia; Ernita Arif; Azwar Azwar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the communication behavior of the kyai with the community at the Nurul Yaqin Islamic boarding school. The focus of the problem of this research is the communication behavior of the kyai with the community at the Nurul Yaqin Islamic boarding school. Researchers used a qualitative study research method with a phenomenological approach. Descriptive method is intended to describe systematically, factually and accurately about the data. Qualitative research aims to gain an authentic understanding of people's experiences, as perceived by the people concerned. The data collection techniques used were in-depth interviews, observation, and document collection. Sources of data are the results of interviews, observation findings in the Pariaman area, and documents with relevance. The technique of determining informants using snowball sampling, in this study is Kyai and the community. The research was conducted at the Nurul Yaqin Islamic boarding school in Padang Pariaman Regency. Kiyai (Buya) teaches religious behavior towards the people of lightness, such as worshiping Allah SWT, respecting each other, and not doing bad deeds that harm others. From religious values, Nurul Yaqin Islamic Boarding School places more emphasis on aspects of the faith as well as other religious fields. This study concludes that the kyai's communication behavior with the Nurul Yaqin Islamic boarding school community.